A Combination of Hill CIPHER-LSB in RGB Image Encryption - Megantara, Rama Aria; Rafrastara, Fauzi Adi; Mahendra, Syafrie Naufal (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2019)
The progress of the development of digital technology today, many people communicate by sending and receiving messages. However, along with extensive technological developments, many crimes were committed. In avoiding these crimes, data security needs to be done. Form of data security in the form of cryptography and steganography. One of the cryptographic techniques is the hill cipher algorithm. Hill ciphers include classic cryptographic algorithms that are very difficult to solve. While the most popular steganography technique is Least Significant Bit (LSB). Least Significant Bit (LSB) is a spatial domain steganography technique using substitution methods. This study discusses the merging of message security with hill cipher and LSB. The message used is 24-bit color image for steganography and text with 32, 64 and 128 characters for cryptography. The measuring instruments used in this study are MSE, PSNR, Entropy and travel time (CPU time). Test results prove an increase in security without too damaging the image. This is evidenced by the results of the MSE trial which has a value far below the value 1, the PSNR is> 64 db, the entropy value ranges from 5 to 7 and the results of travel time <1 second.